Evaluating the effect of an aqueous extract of Pistia stratiotes Linn (Araceae) on tear secretion and tear film stability in ICR mice - Samuel Abokyi,, George Asumeng Koffuor, Elvis Ameyaw Ofori, Ama Kyerea Thomford, Kweku Antwi Osei (Journal of Applied Pharmaceutical Science, 2014)
Management of allergic conjunctivitis with conventional anti-allergic drugs usually cause the discomfort of dry eyes. This study, therefore, sought to evaluate the effect of Pistia stratiotes, a herbal remedy with anti-allergic properties, on tear secretion and tear film stability. ICR mice were grouped and treated with 5 mg/kg cetirizine, 10 mg/kg prednisolone, 100 mg/ kg leaf extract of P. stratiotes (LEPS), or 2 ml/kg normal saline per os for 7 consecutive days. With the phenol red thread test and the determination of fluorescein tear film break-up time, tear secretion and tear film stability before and after drug interventions were determined. Results recorded indicated that tear secretion and tear film stability declined significantly with cetirizine treatment (1.188 ± 0.4369 mm; P ≤ 0.05, and 2.688 ± 0.6185 s; P ≤ 0.001 respectively), while only tear secretion reduced significantly (P ≤ 0.05) in mice treated with prednisolone (0.9380 ± 0.4422 mm). Treatment with LEPS showed no significant effect (P > 0.05) on tear secretion and tear film stability (0.7050 ± 0.4236 mm, and 0.9790 ± 0.6145 s respectively); comparable to normal saline treatment. Per the findings, Pistia stratiotes does not affect tear secretion and tear film stability and hence is not likely to exhibit the adverse effect of dry eyes, as conventional anti-allergic drugs do, in the management of allergic conjunctivitis.
Keywords: Dry eyes, Phenol red thread test, Fluorescein tear film break-up time, Allergic conjunctivitis.